TO EXPLAIN THE NATURE OF CORE POROSITY USING RESULTS OF PETROGRAPHY ANALYSIS - Junita Trivianty Musu (Testing Center for Oil and Gas LEMIGAS, 2007)
The Permian to Triassic Tirrawarra Sandstone succession in the Cooper Basin of CentralAustralia is characterized by its low permeability. Ambient core porosity averages8.96% and ambient permeability 0.9 mD. Most samples studied have permeabilities lessthan 3mD. Despite its overall poor reservoir characteristics, the Tirrawarra Sandstone isone of the major oil and gas targets in Australia. A total of 17 core plugs from 6 wellswere studied petrographically using optical petrography, SEM and XRD. These resultswere integrated with core analysis data.Petrographic study revealed the diagenetic events, mainly mechanical and chemicalcompaction, cementation and alteration have modified the reservoir quality. Ductile componentssuch as rock fragments, clay and matrix influence mechanical compaction, whichare the main cause of reservoir quality reduction. Quartz cementation and clay distributionalso affected the porosity, but particularly permeability. Mechanical compaction aswell as quartz cementation have reduced and blocked pore-throats to isolate intergranularpores. The alteration of feldspar to kaolin has changed intergranular porosity tomicroporosity. Illite occurs as either cement, alteration of rock fragments or kaolinite. Allof these diagenetic events also affect fluid movement in the reservoir.This paper presents the evaluation of the determination of effectiveness of porosity inthe delivery of gas from sandstone reservoir in the Cooper Basin using integrated petrographyanalysis and core measurements.